Similarity of geleophysic dysplasia and weill–marchesani syndrome. Issue 12 (24th September 2013) - Kochhar, Aaina; Kirmani, Salman; Cetta, Frank; Younge, Brian; Hyland, James C.; Michels, Virginia
Abstract : The acromelic dysplasias comprise short stature, hands and feet, and stiff joints. Three disorders are ascribed to this group, namely Weill–Marchesani syndrome, geleophysic dysplasia, and acromicric dysplasia, although similar in phenotype, can be distinguished clinically. Weill–Marchesani syndrome, on the basis of microspherophakia and ectopia lentis; geleophysic dysplasia by progressive cardiac valvular thickening, tracheal stenosis, and/or bronchopulmonary insufficiency, often leading to early death. Microspherophakia has not been reported previously in geleophysic dysplasia. Mutations in FBN1, ADAMTS10, or ADAMTS17 cause Weill–Marchesani syndrome by disrupting the microfibrillar environment, while geleophysic dysplasia is associated with enhanced TGF‐β signaling mediated through mutations in FBN1 or ADAMTSL2 . We studied a 35‐year‐old woman with geleophysic dysplasia, with short stature, small hands and feet, limitation of joint mobility, mild skin thickening, cardiac valvular disease, restrictive pulmonary disease, and microspherophakia. Sequencing of ADAMTSL2 demonstrated two changes: IVS8‐2A>G consistent with a disease‐causing mutation, and IVS14‐7G>A with potential to generate a new splice acceptor site and result in aberrant mRNA processing. The unaffected mother carries only the IVS8‐2A>G transition providing evidence that the two changes are in trans ‐configuration in our patient. © 2013 Wiley Periodicals, Inc.